1, 2, 3, 4, 6-Pentakis[-O-(3, 4, 5-trihydroxybenzoyl)]-α, β-D-glucopyranose (PGG) analogs: design, synthesis, anti-tumor and anti-oxidant activities. (22nd July 2016) - Shaikh, Qurat-ul-ain; Yang, Meiting; Memon, Khadim Hussain; Lateef, Mehreen; Na, Du; Wan, Shengbiao; Eric, Deslandes; Zhang, Lijuan; Jiang, Tao
Highlights: A series of new benzoic and cinnamic acid analogs of PGG were synthesized. The SAR of PGG analogs for antitumor and antioxidant activity has been studied. PGG had highest cytotoxicities inHCT116 andA549 cells. Pentavanilloylglucose was most effective at killingHT29 andH1299 cells. Different molecular targets might be involved for antitumor and antioxidant activities. Graphical abstract: Abstract: 1, 2, 3, 4, 6-Pentakis[-O-(3, 4, 5-trihydroxybenzoyl)]-α, β-D-glucopyranose (PGG)12 has been reported for its antioxidant activities, where the free OH groups in PGG seem to be critical for activities. To explore PGG-based compounds as chemotherapeutic agents and to analyze the contribution of specific OH groups in PGG for anti-cancer activities, we designed and synthesized a series of 27 benzoic and cinnamic acid analogs of PGG. These analogs were tested for cytotoxicities against two human lung (A549 andH1299 ) and two human colon (HCT116 andHT29 ) cancer cell lines. Compound12 (PGG) had highest cytotoxicities againstHCT116 andA549 cells with IC50 of1.61 µM and3.02 µM, respectively. In contrast, the compound16 (1, 2, 3, 4, 6-pentakis[-O-(4-hydroxy-3-methoxybenzoyl)]-α, β-D-glucopyranose, PVG) was most effective at killingHT29 andH1299 cells with IC50 of1.76 µM and3.65 µM, respectively, indicating the mutual contribution of m -methoxy and p -hydroxy groups to the observed cytotoxicities. Moreover, cinnamic acid analogs were less active than the benzoic acid analogs evidenced by higher IC50 values. Furthermore, in cinnamic acid analogs the hydrogenation of double bond to saturated 2-C side chain enhance the cytotoxicities in all four cell lines. Compounds also possess good anti-oxidant and reducing activities. Compound12 and26 show the highest antioxidant and reducing activities.